Unusual presentation of hepatic vascular tumors as fulminant hepatic failure - Meral AKDOĞAN; Ahmet GÜRAKAR; Stan SHARAGO; Karim El-SAHWI; Jeff CARLSON RN; Anthony SEBASTIAN; Urooj AHMED; Harlan WRIGHT; Bakr NOUR (Turkish Journal of Gastroenterology, 2019)
-